Sistem Informasi Alih Kredit Mata Kuliah (SIAKSI) untuk Mahasiswa berbasis Web - Dian Nurdiana; Adhi Susilo; Dwi Astuti Aprijani; Andri Suryadi (Universitas Hamzanwadi, 2022)
Currently, the Open University Information Systems study program has developed a credit transfer application but it is not optimal. Administrators and assessing lecturers must manually input student credit transfer applications and students cannot monitor the credit transfer application process. The purpose of this study is to create an information system for transferring course credits for students so as to overcome problems in current business processes. The software development method uses Waterfall which consists of needs analysis, design, coding and testing. The analysis stage uses the PIECES method which examines aspects of performance, information, economy, security, efficiency and customer service. The business process design is depicted using the Use Case and Activity Diagrams, while the system testing uses Black Box. Our findings are in the form of an information system that can help the academic process to transfer course credits. In addition, the results of blackbox testing, all components in this system have run well according to the previously built design. Therefore, the existence of this system can help the campus to record students who will be about credits in the courses they take